Understanding the supportive care needs of Hispanic men cancer survivors. Issue 1 (2nd January 2017) - Martinez Tyson, Dinorah (Dina); Vázquez-Otero, Coralia; Medina-Ramirez, Patricia; Arriola, Nora B.; McMillan, Susan C.; Gwede, Clement K.
ABSTRACT: Objective. To date, there is a paucity of research and information on Hispanic men cancer survivors (HMCS), who comprise part of the largest and fastest growing racial/ethnic minority group in the country. The purpose of this paper is to provide a deeper understanding of the supportive care needs of HMCS. Design. Three focus groups with a community sample of HMCS ( n = 18) and interviews with providers ( n = 5) were conducted to explore the supportive care needs of Hispanic men who had been diagnosed with cancer within the last five years. The data were analyzed using applied thematic analysis techniques. Results. Findings from focus groups and interviews are presented concurrently. The overarching themes that emerged were the need for: culturally sensitive cancer care and better communication with providers; cancer treatment-related information and comprehensive survivorship care; support and to connect with other cancer survivors and the need to negotiate changing gender role expectations and still provide for their family. Conclusion. Study findings contribute to the literature by presenting the supportive care needs of HMCS and illustrate the need for continued research to address disparities in access to cancer information and in the provision of culturally sensitive care. We provide recommendations and suggestions to address the supportive care needs of HMCS.